An overview of the Canadian landscape on the use of restorative therapies for erectile dysfunction and Peyronie’s disease - Shah, Jainik; Fidel, Maximilian G.; Bal, Dhiraj S.; Kharazi, Armin; Roque, Connor F.; Ko, Yool; Sidhom, Karim; Bouhadana, David; Petrella, Francis; Patel, Premal (Canadian Urological Association Journal, 2024)
INTRODUCTION: Restorative therapies (RTs), including low-intensity shockwave therapy (Li-SWT) and platelet-rich plasma (PRP), aim to restore natural erectile function. Many clinics offer these therapies for erectile dysfunction (ED) and Peyronie’s disease (PD) with direct-to-consumer (DTC) marketing. This study sought to investigate the landscape of RTs within Canadian clinics. METHODS: Online searches were made to identify clinics offering Li-SWT and/or PRP as an RT for treating ED and PD in Canada. Public websites were analyzed, followed by calling clinics for data on cost, treatment protocols, clinic ownership, success rates, and adjunctive therapies. RESULTS: A total of 107 clinics were identified online, with a 68.2% call response rate (n=73). Of the respondents, 56 and 40 clinics provided Li-SWT and PRP therapies, respectively, with 23 clinics offering both. All clinics reported using RTs for ED, with 21 clinics offering Li-SWT and 22 clinics providing PRP for PD. Forty-three clinics provided costs and protocols for Li-SWT, while 33 clinics did so for PRP. The average cost ± standard deviation (CAD) of six sessions of Li-SWT was $2167.24±936.11 and one shot of PRP was $1478.68±591.98. Most (60.3%, n=44) clinics reported physician ownership, with a majority (n=28) being family medicine-trained. Seven clinics did not provide data and 22 were non-physician-owned. Ten clinics provided success rates, with an average of 87.3%. CONCLUSIONS: Despite limited data supporting their routine clinical use, many clinics across Canada offer RTs for ED and PD with varying treatment protocols and increased costs. Further research is required to evaluate the efficacy of RT for ED and PD.